Perlindungan Hukum pada Tenaga Kerja yang Mengalami Pemutusan Hubungan Kerja (PHK) karena Dampak Pandemi Covid-19 - Cahyo Adhi Nugroho (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2023)
The background of this research is that in the city of Semarang, the discussion on the issue of Termination of Employment (PHK) is a complex problem, because it has a relationship with economic and psychological problems for workers affected by layoffs. Economic problems because layoffs will cause a loss of income that should have been received by the workforce before the layoff occurred, of course this will become a new problem for the workforce. Writing this thesis discusses legal protection for workers/laborers affected by layoffs caused by the COVID-19 Pandemic, as well as an understanding of the rules regarding the rights of affected workers (PHK) according to the provisions of Law no. 13 of 2003 concerning Manpower. The method used is normative juridical and empirical juridical approaches, to analyze the data is qualitative analysis, namely data that is arranged systematically and analyzed qualitatively in order to achieve clarity of the problem to be discussed and the results are set forth in the form of a thesis. Legal protection for workers/laborers due to the impact of the Covid-19 Pandemic, namely contained in Article 164 Paragraph (3) of Law Number 13 of 2003 concerning Manpower with legal protection in the form of giving severance pay, giving awards or service money during the worker/labourer's working period , and the granting of compensation rights for the impact of the layoffs.